1999
DOI: 10.1128/jcm.37.12.3934-3939.1999
|View full text |Cite
|
Sign up to set email alerts
|

vanA and vanB Incorporate into an Endemic Ampicillin-Resistant Vancomycin-Sensitive Enterococcus faecium Strain: Effect on Interpretation of Clonality

Abstract: Clonal spread and horizontal transfer in the spread of vancomycin resistance genes were investigated. Multiplex PCR, pulsed-field gel electrophoresis (PFGE), hybridization of enterococcal plasmids with the vanA and vanB probes, and sequencing of a fragment of vanB were used in the analysis. Before May 1996, 12 vancomycin-resistant Enterococcus faecium (VRE) isolates were found in Finland. Between May 1996 and October 1997, 156 VRE isolates were found in the Helsinki area. Between December 1997 and April 1998, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 26 publications
4
22
0
1
Order By: Relevance
“…However, a possibility of the presence of VanB could not be eliminated in these bacteria. Previous studies have reported the presence of both VanA and VanB in the same isolate (Suppola et al 1999). The VanA phenotype expressing high-level Vn and Tp resistance is carried on Tn1546-like elements (Derlot and Courvalin 1991;Arthur et al 1996;Garnier et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…However, a possibility of the presence of VanB could not be eliminated in these bacteria. Previous studies have reported the presence of both VanA and VanB in the same isolate (Suppola et al 1999). The VanA phenotype expressing high-level Vn and Tp resistance is carried on Tn1546-like elements (Derlot and Courvalin 1991;Arthur et al 1996;Garnier et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Most likely, therefore, they were introduced to the study hospital shortly before first detection. Acquisition of vanA genes has been described in ARE [29]. Hospital-wide surveillance for more than four years found no evidence for repeated introduction of these two epidemic STs into the hospital from the environment, but they were detected in other hospitals between 2012 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ever growing subtypes within the vanD‐group has already emphasized the need for consensus D‐primers (14A). VanA and VanB‐phenotypes are the most commonly encountered forms and clinically the most important due to their epidemic appearance in the clinical setting (159, 167). (i) The VanA‐type of resistance is characterised by inducible high‐level resistance to both vancomycin and teicoplanin.…”
Section: Detection Of Glycopeptide Resistance In Enterococci and Stapmentioning
confidence: 99%